Implementasi Model Pembelajaran Kooperatif pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti dalam Meningkatkan Minat Belajar Siswa Kelas XI SMAN 1 Tenjolaya: Implementation of Cooperatif Learning Models in Islamic Religious and Character Education Subjects in Increasing Learning Interest in Class XI Students at SMAN 1 Tenjolaya - Siti Sahidah Mardiah; Moch. Yasyakur; Samsuddin, Samsuddin (Litera Academica Publishing, 2024)
The purpose of this research is to explore the effectiveness of the cooperative learning model in creating a more interactive and collaborative learning environment. The methodology used in this research is a qualitative approach involving in-depth interviews and classroom observations, engaging teachers and eleventh-grade students. The findings of the research indicate that the cooperative learning model successfully enhances students' interest in learning, with students becoming more active and engaged in the learning process. However, challenges also arise, particularly for shy students or those who struggle to interact. The conclusion of this research emphasizes that despite some obstacles, the implementation of this model yields positive results in creating a pleasant and productive learning atmosphere. The implications of this research contribute significantly to the development of PAI and Character Education, encouraging teachers to adopt cooperative methods and consider students' characteristics. Thus, this research not only offers practical strategies for educators but also enriches the literature on innovative learning approaches in the context of Islamic education.